One-micron resolution optical coherence tomography (OCT) in vivo for cellular level imaging - Gu, Jun (2015)
We developed a spectral domain OCT system combining two NIR, CW light sources of different spectral range. Its resolving power is validated by visualizing the cellular structures of zebra fish larvae in vivo. An NIR extended illumination from 755-1100 nm is achieved. The axial resolution is 1.27 μm in air, corresponding to 0.93μm in tissue (n=1.36), which is the highest axial resolution using NIR, CW laser sources up to date to the best of our knowledge. In vivo imaging is conducted to demonstrate the resolving power of proposed one-micron resolution OCT system. The top and bottom surfaces of individual disk-like red blood cell is reliably visualized, as well as flat, spindle shaped endothelial cells lining along the luminal surface of the blood vessel wall. This study provides a viable solution for cellular and subcellular level OCT imaging system which is also very competitive in cost.